Hyperargininemia: a rare diagnosis in adulthood - Carolina Freitas Henriques; Rui Fernandes; Francisco Barreto; Rubina Miranda; Teresa Carolina Aguiar (European Journal of Case Reports in Internal Medicine, 2024)
Background: Hyperargininemia is a rare inherited metabolic disorder of the urea cycle with an autosomal recessive transmission. It occurs due to a deficiency of the enzyme arginase I and causes progressive neurological damage. Very few cases are diagnosed in adulthood, with the majority being diagnosed before the age of 4. Currently, this condition is diagnosed by a mass spectrometry technique in neonatal screening, which has been implemented in Portugal since 2007; births before that were not screened for this entity. Case description: We present a case of a 23-year-old woman referred to the internal medicine and neurology departments with a history of two hospital admissions for rhabdomyolysis at the age of 18, consanguineous parents, learning difficulties and multiple falls since the age of 8. In addition, the patient also had behavioural changes so she had psychological counselling at school, but lacked family support. Neurological examination showed mild proximal paraparesis, and spastic and paraparetic gait. The aetiological study revealed a pathological variant in homozygosity ARG1 and increased blood levels of arginine. Therefore, the diagnosis of hyperargininemia was confirmed. Conclusions: Compared to other urea cycle disorders, hyperargininemia is the rarest one. It is important to recognise the characteristic clinical features and diagnose it early because a favourable outcome can be achieved with appropriate treatment. This case shows a delayed diagnosis of hyperargininemia and highlights the importance of the internist’s role in diagnosing rare diseases.